Improving collegiate student-athletes’ well-being: exploring the roles of openness to experience, knowledge sharing and perceived coaching effectiveness - Ni, Peihao; Feng, Ligang (Frontiers in Psychology, 2023)
Introduction Collegiate student-athletes often encounter various stressors stemming from academic study and athletic training, which can potentially have negative effects on their well-being. This study investigates how collegiate student-athletes’ openness to experience and their engagement in knowledge sharing influence their well-being, as well as the moderating role of perceived coaching effectiveness. Methods To examine these relationships, we propose and test a conceptual framework using an online survey conducted among collegiate student-athletes from a southeastern province of China. The participants consisted of 484 collegiate student-athletes who voluntarily participated in the study. We used regression analysis and mediation analysis to test the proposed relationships among the variables. Results Openness to experience has a positive impact on knowledge sharing (β = 0.552, p < 0.05); knowledge sharing with peers positively affects collegiate student-athlete well-being (β = 0.415, p < 0.05) and mediates the relationship between openness to experience and collegiate student-athlete well-being (β = 0.086, p < 0.05). Perceived coaching effectiveness positively moderates the relationship between openness to experience and knowledge sharing (β = 0.170, p < 0.05). Discussion Our study contributes to the collegiate student-athlete literature by shedding light on the factors that influence their well-being, with insights that bear important managerial implications for universities and coaches.